Hurst's the heart - Fuster, Valentín (McGraw-Hill, 2004)
This description refers to the second volume of a two-volume set. The most comprehensive and current resource on the heart! This unparalleled text continues to focus on patient care rather than the scientific aspect of the specialty. Thoroughly revised, this new edition is 33% new and updated. With continued emphasis on diagnosis and treatment, Hurst’s THE HEART, 11/e features greater use of tables, charts and figures, as well as current ACC/AHA guidelines, interpretations of clinical trials and cardiology data found in the Human Genome Project, and more information on MRI and PET.
Keywords: kardiovaskulární nemoci; diagnostika; DIAGNÓZA KARDIOVASKULÁRNÍ; Cardiovascular Diseases; Heart Diseases; kardiologie; nemoci srdce